Öğretmenlik Meslek Kanununun İlkokulda Görev Yapan Okul Müdürlerinin Görüşleri Doğrultusunda Değerlendirilmesi - Arabacı, İmam Bakır; Güzelgörür, Fatma; Sever, Rukiye Çevik; Kelepçe, Osman; Sever, Akif (Hayrullah KAHYA, 2023)
Bu çalışma, Öğretmenlik Meslek Kanunu’na ilişkin ilkokul müdürlerinin görüşlerini incelemeyi amaçlamaktadır. Araştırma nitel araştırma yöntemlerinden olgubilim (fenomenoloj) desenle yürütülmüştür. Araştırmacılar tarafından geliştirilen görüşme formu ile farklı ilkokullarda görev yapan okul müdürleri ile görüşmeler yapılmıştır. Araştırmanın çalışma grubunu 2022-2023 yılında Elâzığ ili Kovancılar ve Karakoçan ilçelerinde farklı ilkokullarda görev yapan 14 okul müdürü oluşturmaktadır. Araştırma verileri, yarı yapılandırılmış görüşme formu aracılığı ile toplanmıştır. Elde edilen veriler içerik analizine tabi tutulmuştur. Okul müdürlerinin Öğretmenlik Meslek Kanunu’na ilişkin görüşleri, kapsam, eksiklikler, öğretmenlerin yeterlik ve yetkinliğine katkı ve öneriler olmak üzere üç tema altında toplanmaktadır. Araştırma sonucunda bazı okul müdürlerinin Öğretmenlik Meslek Kanunu’nun hizmet koşulları ve öğretmenlerin özlük haklarında ciddi iyileştirmeler getirdiğini, bazı okul müdürlerinin ise kariyer, özlük ve sosyal haklarda iyileştirme, geliştirme getirmediğini, öğretmenler, veli ve okul yöneticileri arasında çatışmalara ve ayrımcılığa neden olduğunu belirttikleri görülmüştür. Okul müdürleri, Öğretmenlik Meslek Kanunu’nun da hizmet yönünden bazı düzenlemelerin yapılmasının uygun olacağını belirtmişlerdir.

This research aims to examine the primary school principals’ opinions with respect to the Teaching Profession Law. The study has been carried out by means of the phenomenological research, one of the qualitative research methods. Interviews have been conducted with school principals working at different primary schools using the interview form developed by the researchers. The study group of the research consists of 14 school principals working at different primary schools in Kovancılar and Karakoçan districts of Elazığ province in 2022-2023. Research data has been collected through a semi-structured interview form. The collected data has been analysed using the content analysis method. The school principals’ opinions regarding the Teaching Profession Law are grouped under three themes: the scope of the law, its shortcomings, its contribution to the competence and competency of teachers, and suggestions. As a result of the research, it has been found that some school principals favour the Teaching Profession Law due to considerable improvements it has introduced to service conditions and personnel rights, while some school principals criticize the law for not making any improvements or developments in career adjustments and personnel and social rights. While the school principals think that increasing salaries through professional career stages will have a positive contribution, it may also cause conflicts and discrimination between teachers, parents and school administrators, which will lead to a negative situation. The school principals have stated that it would be appropriate to make some arrangements in terms of service conditions in the Teaching Profession Law.
Evaluation of the Teaching Profession Law in Line with the Opinions of Primary School Principals
Keywords: Educational Sociology; Eğitim Sosyolojisi